A cross-sectional study of prevalence and determinants of depression among stroke patients - Litton, Jim; S., Lokesh (International Journal of Advances in Medicine, 2016)
Background: The association between depression and stroke is well known. Few studies show that lesion side and site are associated with post-stroke depression (PSD), but there exists a vast discrepancy in the results among various studies. The prevalence of post stroke depression also varies widely. In India there is paucity in the amount of literature in this context. Early detection of depression is of prime importance for better outcomes. The study was mainly intended to find out these variations. Methods: To study the prevalence of post stroke depression, the neuroanatomical correlation of post stroke depression and impact of comorbid conditions in post stroke depression. This cross sectional study was designed at medicine department of MGMCRI, Puducherry, India. All adult patients with stroke (>40 years) presenting to the emergency medical services (EMS) and department of medicine were enrolled. Patients fulfilling the inclusion criteria were taken up for the study after obtaining consent. Data about pre-existing comorbid illness such as diabetes, hypertension, ischaemic heart disease and substance abuse like smoking, alcohol use were collected. Complete physical examination and CNS examination were performed. The findings of CT brain were documented including the site of lesion. Depression was assessed on the 14th day after stroke using PHQ-9 questionnaire. Chi square and regression analysis were employed for statistical analysis. Results: The mean age of subjects in this study was found to be 63.84±11.40 years. The prevalence of severe depression in this study was 47%. Milder form of depression was found in 53% of the subjects. Of the total population studied, statistically significant severe depression was associated with patients who had lesion on left hemisphere. Conclusions: Post stroke depression is more associated primarily with left sided hemispheric lesions. The prevalence of significant post stroke depression in present study was 47%. This study highlights the importance of screening stroke patients for depression. Early intervention of post stroke depression can lead to better outcomes.